Health care utilization of refugees - Thomas Schober; Katrin Zocher (Johannes Kepler University of Linz, Department of Economics, 2018)
European countries experienced significant inflows of migrants in the past decade, including many refugees coming from regions engaged in armed conflicts. While previous research on migrant health largely focused on economic migration, empirical evidence on the health of refugees is sparse. We use administrative data from Austria to differentiate between economic migrants and refugees and analyze their health care expenditures in comparison to natives. The results distinctly show different expenditure patterns. Unlike economic migrants, we find substantially higher expenditures for refugees, most pronounced in the first year upon arrival. The difference is not explained by specific diseases or individual refugee groups, indicating a, generally, inferior health status. Further, by using the quasi-random placement of refugees as a natural experiment, we show that characteristics of the local health care sector do not have a significant effect on expenditure levels.
Keywords: 330